The Construction Technology of Roof Steel Structure in YanCheng NanYang Airport - Qin Yang; Shaole Yu; Xuewei Zhang; Zhijun Wang; Junsheng Yan; Xinxi Chen (Advances in Civil Engineering)
The roof steel structure in the Terminal 2 building of YanCheng NanYang Airport has a large span and a considerably difficult construction. According to the project characteristics, the construction scheme of the roof steel structure follows the principle of subareas and substeps, with the truss lifting in segmentation. To ensure construction safety, a construction monitoring scheme was adopted in this project. According to the layout of the roof steel structure, a total of 10 monitoring points are arranged to monitor the stress of the roof steel structure during the construction process. This paper first gives a brief introduction to the general situation regarding the engineering, followed by a detailed description of the construction scheme of such a roof steel structure. Then, the monitoring results, including monitoring of the main truss’ stress and column head, are introduced. The monitoring results revealed that the variation of stress in monitoring points followed the same trend as the monitoring data. The maximum stress was 166.6 MPa according to the monitoring results, which indicate that the stress of the roof steel structure is in the elastic stage during the construction process and the construction scheme is feasible.